2017
DOI: 10.1007/s00221-017-4911-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in equiprobable auditory Go/NoGo task: effects on N2 and P3

Abstract: The Go/NoGo variants of the auditory event-related potentials were shown promising for clinical researches; however, prior to the wider application, it is important to evaluate potential modulating factors. We aimed to evaluate gender effect on the behavioral and electrophysiological responses in an auditory equiprobable Go/NoGo task. The auditory equal probability Go/NoGo paradigm with two types of stimuli was presented to 79 healthy subjects (40 females and 39 males, age 18-30 years) during EEG recording. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 72 publications
1
26
0
Order By: Relevance
“…Six EEG studies examined sex differences in regional brain activity in the domain of response inhibition. Three of these studies used a Go/ No‐Go task (Knezevic, 2018; Melynyte et al., 2017; Ramos‐Loyo et al., 2016). In the remaining studies, such sex‐dependent activity was assessed in two studies using the Flanker Task (Clayson et al., 2011; Larson et al, 2011), and one study using the Continuous Performance Task (Omura & Kusumoto, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Six EEG studies examined sex differences in regional brain activity in the domain of response inhibition. Three of these studies used a Go/ No‐Go task (Knezevic, 2018; Melynyte et al., 2017; Ramos‐Loyo et al., 2016). In the remaining studies, such sex‐dependent activity was assessed in two studies using the Flanker Task (Clayson et al., 2011; Larson et al, 2011), and one study using the Continuous Performance Task (Omura & Kusumoto, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…[11] The study by Melynyte et al, which found longer latencies in females, included only young female subjects (age range: 18-29 years), which is comparable to our sample. [12] More studies are needed in this specific age group with more sample size to test the consistency of this finding. Gender differences in P300 have been attributed to variations in processing strategies, anatomical differences such as larger corpus callosum in females, different neuronal maturity rates, and hemispheric asymmetry between males and females.…”
Section: Gender Differences In Auditory P300 Event-related Potential mentioning
confidence: 88%
“…Hypothetically, the absence of a stimulus‐locked N2c in this study could suggest that the typical Go N2c is a response‐related component, as anticipated. The small diffuse topography of the auditory N2c and its usual latency ~250 ms poststimulus (e.g., Fogarty et al, ; Melynyte, Ruksenas, & Griskova‐Bulanova, ) could suggest that it reflects a smearing of RN2 in stimulus‐locked data, which would explain why larger RTV has been linked to smaller stimulus‐locked N2c amplitudes (Fogarty, Barry, De Blasio, & Steiner, ). If this is the case, N2c's role in target stimulus processing would be questionable (cf.…”
Section: Discussionmentioning
confidence: 99%